Understanding the Importance of Adult and Community Education (Indian Journal of Management and Language (IJML), 2025)
In India, in mainly communities, belonging to deprived, marginalized and economically weaker sections, the individuals are normally unable to pursue educational goals. The experience various reasons, which enable them to discontinue their education. Some of the reasons are, scarcity of financial resources, learning disabilities, health problems and illnesses, inability to transfer from one place to another, and so forth. These are experienced in a major or minor form. Hence, all types of problems, major and minor give rise to impediments within the course of achievement of different types of educational goals. The individuals, belonging to all communities and socio-economic backgrounds have recognized the meaning and significance of education. They have formed the viewpoint that education is the instrument, which not only imparts information in terms of academic subjects and lesson plans, but also in terms of ways that are necessary to emerge into moral and ethical human beings. Hence, in urban and in rural communities, there are adult education centres. These are focused on imparting information among adults, who have dropped out before their educational skills are honed. Therefore, it is understood on a comprehensive basis that adult education is facilitating in augmenting knowledge, competencies and abilities among individuals. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of adult and community education, measures to be put into practice in leading to up-gradation of adult and community education and advantages of adult and community education.